The effect of pH treatment and refrigerated storage on natural colourant preparations (betacyanins) from red pitahaya and their potential application in yoghurt - Gengatharan, A.; Dykes, Gary; Choo, W. (Elsevier, 2017)
© 2017 Elsevier Ltd The present study investigated the effects of pH (pH 3, 4, 5 and 6) treatment and refrigerated storage at 4 °C on the stability of colourant preparations from red pitahaya and compared to a commercial colourant preparations from red beet, E-162. The potential of using colourant preparations from red pitahaya in yoghurt and compared to E-162 was also investigated. Immediately after pH treatment, the highest percentage of reduction of betacyanin was observed at pH 3. The loss of betacyanin content in yoghurts containing colourant preparations from red pitahaya and E-162 over 14-days of refrigerated storage was 1.0± 0% and 1.6± 0.1%, respectively. Syneresis in yoghurt containing colourant preparations from red pitahaya and E-162 were lower than that of plain yoghurt. The addition of betacyanins from red pitahaya or E-162 increased the free radical scavenging activity in yoghurts. The total microbial counts of Streptococcus thermophilus and Lactobacillus delbrueckii ssp. bulgaricus in yoghurts containing colourant preparations from red pitahaya and E-162 were in the 10 8 –10 9  CFU/mL range. The colour acceptability of yoghurt containing colourant preparation from red pitahaya was similar with E-162 and a commercial strawberry flavoured yoghurt suggesting its potential application as a natural functional colourant.